Shark - Ross, Jeff, 1973- (Orca soundings., 2018)
Seventeen-year-old Mark "Shark" Hewitt is good at playing pool. Really good. When he, his mom and sister move to a new town, Mark immediately seeks out the local pool hall. He loves to play, but even more than that, he just loves hanging out with the regulars. It reminds him of good times with his dad, who is no longer in the picture. When one of the patrons notices Mark's natural gift for the game, he forces Mark to use his talent for profit. Now Mark has to find a way to get out from under this sleazeball's thumb and protect his family.